Effect of different root canal sealers on periapical repair of teeth with chronic periradicular periodontitis - Filho, M. Tanomaru; Leonardo, M. R. [UNESP]; Silva, L. A. B.; Utrilla, L. S. (Wiley, 1998)
Teeth with induced chronic periradicular periodontitis in dogs were root canal treated. After the biomechanical preparation, using K files and 5.25% sodium hypochlorite as the irrigant solution, all root canals were dressed with an antibacterial dressing based on calcium hydroxide, which was left in place for 7 days. After this time, the root canals were obturated with lateral condensation of cold gutta-percha with either a calcium hydroxide root canal filling material (Sealapex) or a zinc oxide-eugenol sealer (Fill Canal). After 270 days, histopathological analysis showed better apical and periapical repair in the teeth obturated with Sealapex (P < 0.05).
Keywords: Calcium hydroxide; Periapical periodontitis; Periapical repair; Root canal filling material